Genome-wide identification of germin-like proteins in peanut (Arachis hypogea L.) and expression analysis under different abiotic stresses - Yang, Qiang; Sharif, Yasir; Zhuang, Yuhui; Chen, Hua; Zhang, Chong; Fu, Huiwen; Wang, Shanshan; Cai, Tiecheng; Chen, Kun; Raza, Ali; Wang, Lihui; Zhuang, Weijian (Frontiers in Plant Science, 2023)
Peanut is an important food and feed crop providing oil and protein nutrients. Germins and germin-like proteins (GLPs) are ubiquitously present in plants playing numerous roles in defense, growth and development, and different signaling pathways. However, the GLP members have not been comprehensively studied in peanut at the genome-wide scale. We carried out a genome-wide identification of the GLP genes in peanut genome. A total of 84 GLPs (AhGLPs) were found in the genome of cultivated peanut. These GLP genes were clustered into six groups. Mainly purifying selection led to gene duplication, and segmental duplication events played a key role in the evolution of AhGLPs. Most AhGLPs possessed a well-maintained gene structure and motif organization within the same group. The promoter regions of AhGLPs contained several key cis-elements responsive to phytohormones, growth and development, defense, and light induction. Totally seven miRNAs from six different families were found targeting 25 AhGLPs. GO enrichment analysis showed that AhGLPs are highly enriched in nutrient reservoir activity, aleurone grain, external encapsulating structure, multicellular organismal reproductive process, and cellular response to acid chemicals, indicating their important biological functions. AhGLP14, 38, 54, and 76 were expressed in most tissues, while AhGLP26, 29, and 62 showed abundant expression in the pericarp. AhGLP7, 20, and 21, etc., showed specifically high expression in embryo while, AhGLP12, 18, 40, 78 and 82 were highly expressed under different hormones, water, and temperature stress. The qRT-PCR results were in accordance with the transcriptome expression data. In short, these findings provided a foundation for future functional investigations on the AhGLPs for peanut breeding programs.